Craniometric and Topographic Analysis of British Shorthair and Scottish Fold Cats Using Three-Dimensional Modelling - Aslan Kanmaz, Yesim; Isbilir, Fatma; Guzel, Baris Can (Wiley, 2025)
Background This study aimed to investigate the craniometric and topographic measurements of the skull and mandible of British shorthair and Scottish fold cats using computed tomography and 3D software. Materials and Methods For this purpose, in a total of 26 cats, 13 British shorthair (7 males and 6 females) and 13 (7 males and 6 females) Scottish fold cats were used in the study. The skulls were scanned with 64-detector multislice Siemens computed tomography devices at 80 kV, 200 MA, 639 mGY and 0.625 mm section thickness. The resulting images were saved in DICOM format. They were modelled and measured with 3D slicer software. Results In the study, surface area measurements were found to be statistically significant in both cat breeds (British shorthair: p < 0.01; Scottish fold: p < 0.05). However, in mandibular measurements, the CAP parameter was statistically significant only in Scottish fold cats (p < 0.01), whereas no significant difference was observed in British shorthair cats (p > 0.05). Conclusions Craniometric and topographical measurements were performed in British shorthair and Scottish fold cats using a 3D model to reveal the differences between male and female. It will also guide the determination of taxonomic locations of these two species and the detection of morphometric differences between the sexes.
Keywords: cat; computed tomography; mandible; skull